Characterization and Identification of a Novel Torovirus Associated With Recombinant Bovine Torovirus From Tibetan Antelope in Qinghai-Tibet Plateau of China - Dai, Xiaoyi; Lu, Shan; Shang, Guobao; Zhu, Wentao; Yang, Jing; Liu, Liyun; Xu, Jianguo (Frontiers in Microbiology, 2021)
Toroviruses (ToVs) are enteric pathogens and comprise three species, equine torovirus (EToV), bovine torovirus (BToV), and porcine torovirus (PToV). In this study, a novel torovirus (antelope torovirus, AToV) was discovered from fecal samples of Tibetan antelopes (Pantholops hodgsonii) with viral loads of 2.10 × 109 copies/g to 1.76 × 1010 copies/g. The genome of AToV is 28,438 nucleotides (nt) in length encoding six open reading frames (ORFs) with 11 conserved domains in pp1ab and a putative slippery sequence (14171UUUAAAC14177) in the overlapping region of ORF1a and ORF1b. Phylogenetic analysis illustrated strains of AToV form a unique clade within ToVs and comparative analysis showed AToV share relatively low sequence identity with other ToVs in six ORFs (68.2% - 91.6% nucleotide identity). These data suggested AToV represents a novel and distinct species of ToVs. Based on the M genes, evolutionary analysis with BEAST of AToV and other ToVs led to a most recent common ancestor estimate of 366 years ago. Remarkably, recombination analysis revealed AToV was the unknown parental ToV that once involving in the recombinant events of HE genes of two Dutch strains of BToV (B150 and B155), which indicated that AToV occurred cross-species transmission and existed both in the Netherlands and China. This study revealed a novel torovirus, a natural reservoir host (Tibetan antelope) of toroviruses for the first time, and appealed to further related studies to better understand the diversity of toroviruses.